Electrostatic properties of human germlines and biodistribution of small biologics - Leticia Maria De Souza Cordeiro; Kelley Christine Atkinson; Argin Aivazian; Patrick Frank Joyce; Fang Jia; Alessandro Mascioni (mAbs)
Off-target biodistribution of biologics bears important toxicological consequences. Antibody fragments intended for use as vectors of cytotoxic payloads (e.g. antibody-drug conjugates, radiotherapy) can accumulate at clearance organs like kidneys and liver, where they can cause dose-limiting toxicities. Renal and hepatic uptakes are known to be affected by protein electrostatics, which promote protein internalization through pinocytosis. Using minibodies as a model of an antibody fragment lacking FcRn recycling, we compared the biodistributions of leads with different degrees of accumulation at the kidney and liver. We identified a positive electrostatic patch highly conserved in a germline family very commonly used in the humanization of approved biologics. Neutralization of this patch led to a drastic reduction in the kidney uptake, leading to a biodistribution more favorable to the delivery of highly cytotoxic payloads. Next, we conducted a high throughput study of the electrostatic properties for all combinations of VH and VL germlines. This analysis shows how different VH/VL combinations exhibit varying tendencies to create electrostatic patches, resulting in Fv variants with different isoelectric points. Our work emphasizes the importance of carefully selecting germlines for humanization with optimal electrostatic properties in order to control the unspecific tissue uptake of low molecular weight biologics.